PENGARUH PRODUK DOMESTIK BRUTO(PDB), KURS, DAN INFLASI TERHADAP TRANSAKSI UANG ELEKTRONIK DI INDONESIA TAHUN 2007-2020 - Yuriza Zahra Cut; Syapsan Syapsan; Darmayuda Darmayuda (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2022)
This research aims to know how the influence of the GDP, exchange rate, and inflation on Electronic Money Transactions in Indonesian in 2007-2020. This research uses independent variables of Gross Domestic Product (GDP), Exchange rate, and Inflation and dependent variable is Elektronic Money Transaction in Indonesian. The data used in this research is annual data from 2007-2020. The analytical method used is descriptive quantitative and analyzed partially or simultaneously with multiple linear regression OLS (Ordinary Least Square) processed by using E-Views 10. The results of shows that the GDP and Exchange Rate simultaneously have a significant effect on electronic money transactions in Indonesia. Meanwhile, GDP have a positive and significant effect on electronic money tansaction in Indonesia, and exchange rate has a negative and significant effect on electronic money transactions in Indonesia, and Inflation have a positive and insignificant effect on electronic money transaction in Indonesia . In addition, it was found that the value of adjusted R2 is 84,65%.Keywords: Electronic Money Transactions, GDP, Exchange Rate, Inflation